Developing and piloting a cross-sectoral hospital pharmacist intervention for patients in transition between hospital and general practice - Charlotte Arp Sørensen; Linda Jeffery; Jannik Falhof; Philipp Harbig; Klaus Roelsgaard; Solveig Gram; Charlotte Olesen (SAGE Publishing, 2023)
Background: Healthcare is challenged by a rapidly growing group of patients with multi-morbidity and polypharmacy. Increasing activity and specialization puts pressure on healthcare sectors. Medication errors in cross-sectoral transition of patients are often seen. The aim of the study was to explore drug-related problems (DRPs) in the transition of patients between sectors and to develop and pilot-test a cross-sectoral hospital pharmacist intervention to overcome some of these problems. Methods: DRPs in cross-sectoral transitions were explored from four perspectives; the literature, the primary and secondary healthcare sector and the patients. An intervention was developed from the findings through co-creation between pharmacists, doctors and a nurse. The intervention was piloted and evaluated from data on the included patients and the activities performed. Results: DRPs in transitions from general practice (GP) to hospital were caused by inadequate focus on updating the Shared Medication Record (SMR). For patients being discharged, DRPs were described with multiple facets; for example, missing information on medication changes, lacking patient involvement and problems with dose-dispensed medicine or electronic prescriptions. An intervention with a pharmacist in a shared employment between Hospital Pharmacy and GP was developed and piloted. The intervention included medication reconciliation and updating SMR for patients referred to hospital; and medication review, overview of medication changes and follow-up telephone calls for patients discharged from hospital. The intervention identified and solved several DRPs; in this way, medication errors were avoided. Access to health records in both sectors was important in the identification and resolution of DRPs. Conclusion: DRPs in cross-sectoral transitions are multifaceted and the experiences depend on the point of view. The cross-sectoral hospital pharmacist intervention identified and solved several DRPs and medication errors were avoided. The intervention made sense to both healthcare sectors and patients. Shared employment and unique access to health records in both sectors showed to be of importance in the identification and resolution of DRPs. Plain language summary Development and pilot-test of a pharmacist intervention for patients in transition between hospital and general practice Background: Healthcare is challenged by a rapidly growing group of patients with multiple chronic diseases treated with several drugs at the same time. The aim of the study was to explore drug-related problems in the transition of patients between the hospital and patients' general practitioner and to develop and pilot-test a pharmacist intervention to overcome some of these problems. Methods: Drug-related problems in patient transitions were explored from the perspectives of the hospital, the general practitioner, the patients and the literature. An intervention was developed from the findings by pharmacists, doctors and a nurse. The intervention was pilot-tested and evaluated from the descriptions of the included patients and activities performed. Results: Drug-related problems in transitions from general practice to hospital were caused by inadequate focus on updating the Shared Medication Record. For patients being discharged, drug-related problems were related to for example missing information on medication changes sparse involvement of the patient in their own treatment problems with medicine dispensed on a dose dispensing machine at the local pharmacy. An intervention with a pharmacist in a shared employment between Hospital Pharmacy and general practice was developed and piloted. The intervention included talking to the patient about their medication and updating the Shared Medication Record for patients referred to hospital medication review, overview of medication changes and follow-up telephone calls for patients discharged from hospital to general practice. The intervention identified and solved several drug-related problems. Access to health records in both the general practice and at the hospital was important in the identification of drug-related problems. Conclusions: Drug-related problems in cross-sectoral transitions are multifaceted. The pharmacist intervention identified and solved several drug-related problems. The intervention made sense to the general practitioner, hospital and patients. Shared employment and unique access to health records in both the general practice and at the hospital showed to be of importance in the identification of drug-related problems.